PENGEMBANGAN BAHAN AJAR INTERAKTIF BERBANTU PLATFORM WIZER.ME MENGGUNAKAN MODEL PENGEMBANGAN ADDIE - Dewi Pratita DP; deskoni; yuliana FH (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2026)
This study aims to develop interactive teaching materials supported by the Wizer.Me platform using the ADDIE model that meets the criteria of validity, practicality, and effectiveness. This study uses the following methods:Research and Development (R&D) with the ADDIE model. Data were collected through expert validation sheets, student response questionnaires, and learning outcome tests. They were then analyzed using quantitative descriptive analysis and a multivariate analysis.normalized gain(N-gain). The results of the study indicate that the developed teaching materials have a very high level of validity, with an assessment of 88.2% from material experts, 89.4% from media experts and 90% from language experts. The level of practicality based on student responses obtained a percentage of 88.24%, with a very practical category. The results of the effectiveness test showed an increase in student learning outcomes with a value of N-gain of 0.79, which is considered high. These findings indicate that the interactive teaching materials based on Wizer.Me meet the criteria of being valid, practical, and effective as an alternative digital teaching material in the Digital Economics Learning course.